Antenatal breastfeeding promotion amongst pregnancies at high-risk for newborn admission to the NICU: A cross-sectional study. (August 2022) - Pylypjuk, Christy; Bokhanchuk, Anna; Day, Chelsea; ElSalakawy, Yasmine; Seshia, Mary M.
Abstract: Objectives: To determine the prevalence and factors associated with antenatal promotion of breastfeeding in high-risk pregnancies. Study design: This was a cross-sectional study of trends in breastfeeding promotion during antenatal consultation of pregnancies at high-risk for newborn admission to the neonatal intensive care unit (NICU) between January 2017 and December 2020. Eligible high-risk pregnant patients undergoing antenatal consultation in a tertiary-level fetal assessment unit were identified using an electronic clinic repository. Consult letters and fetal assessment reports were reviewed to determine baseline demographics, pregnancy history, fetal findings, and communication about breastfeeding. Descriptive and inferential statistics were used to present findings and compare outcomes between groups. Results: 316 pregnancies were included for final analysis. The mean maternal age was 28.7 years (SD 6.2) and 65 % were multiparas. Median gestational age at time of antenatal consult was 32 weeks [IQR 29–34]. The main indication for consultation was fetal anomalies (72.8%), namely cardiac defects (21.2 %). There was a significant improvement in prevalence of antenatal discussions about breastfeeding over the study period, from 48.8 % early in the study period compared to 73.7 % in the past year (p = 0.036). However, amongst consults where breastfeeding was discussed, almost one-quarter (23.8 %) of patients indicated that they were not planning on breastfeeding postnatally. Conclusion: There has been a significant improvement in promoting breastfeeding antenatally amongst high-risk pregnancies. However, no follow-up or supports were offered to one-quarter of patients who indicated no intention of breastfeeding or using donor milk postnatally. Ongoing work is required to further advance breastfeeding promotion antenatally, increase parental supports and education, and optimize breastfeeding rates postnatally for improving outcomes of this high-risk group. Highlights: While there has been a significant improvement in antenatal breastfeeding promotion amongst high-risk pregnancies, it is still missing in almost one-quarter of patients. There are no obvious demographic or clinical differences between high-risk patients that received antenatal breastfeeding promotion versus those that did not, suggesting that a more standardized approach to antenatal discussions about infant feeding could improve breastfeeding success in the NICU. Ongoing work is required to further improve breastfeeding promotion antenatally along with additional postnatal supports to enhance breastfeeding success.